2016
DOI: 10.1007/s13205-016-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

High-quality metagenomic DNA from marine sediment samples for genomic studies through a preprocessing approach

Abstract: Recent advances in culture-independent studies of microbes had proved to be more reliable and efficient than the conventional ones. The isolation of good quality and quantity of total community DNA are one of the major hurdles in this endeavour. Shearing of DNA during the extraction process and the co-extraction of inhibitory compounds reduce the quality of the isolated nucleic acids making it unsuitable for the construction of large insert metagenomic libraries. In the present study, a multi-level filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Sediment samples were suspended in sterilized virus free seawater and subjected to low speed (320 × g ) centrifugation for the removal of coarse sediment particles followed by high speed (9000 × g ) centrifugation for collecting the fine sediment fraction with bacteria. The supernatant was subjected to sequential filtration using 0.8 μ, 0.45 μ and 0.22 μ filter membranes for the separation of bacterial fraction [5] . Fine sediment obtained after high speed centrifugation and the residue on filter membranes were used for metagenomic DNA extraction as per modified Zhou et al [6] protocol.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Sediment samples were suspended in sterilized virus free seawater and subjected to low speed (320 × g ) centrifugation for the removal of coarse sediment particles followed by high speed (9000 × g ) centrifugation for collecting the fine sediment fraction with bacteria. The supernatant was subjected to sequential filtration using 0.8 μ, 0.45 μ and 0.22 μ filter membranes for the separation of bacterial fraction [5] . Fine sediment obtained after high speed centrifugation and the residue on filter membranes were used for metagenomic DNA extraction as per modified Zhou et al [6] protocol.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The samples were then suspended in a buffer consisting of 10 mM EDTA, 50 mM Tris-HCl, 50 mM Na2HPO4•7H2O at pH 8.0 to remove PCR inhibitors (Zhou et al 1996;Poulain et al, 2015). Genomic DNA was extracted from both the non-processed and filtered subsamples following the protocol of Zhou et al (1996) (as employed in Solomon et al, 2016). The DNA extracted from non-processed sediment subsamples were combined accordingly before amplification.…”
Section: Dna Extraction Pcr Amplification and Sequencingmentioning
confidence: 99%
“…Most of the studies on applying pre-processing sediment samples by sequential membrane filtration focused on the quality assessment and efficiency of the extracted metagenomic DNA. Solomon et al (2016) demonstrated that community DNA with minimal shearing was obtained from pre-processing marine sediment samples and performed PCR amplification of the 16S rDNA gene to confirm that the filtration method isolated high-quality DNA. A similar protocol was employed to process arctic sediment samples to characterize the bacterial community structure by 16S rDNA amplicon sequencing (Kachiprath et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations